Molecular detection of blaTEM-encoding genes in multidrug-resistant Escherichia coli from cloacal swabs of ducks in Indonesia farms - Susmitha Nur Ahadini; Wiwiek Tyasningsih; Mustofa Helmi Effendi; Aswin Rafif Khairullah; Muhammad Khaliim Jati Kusala; Ima Fauziah; Latifah Latifah; Ikechukwu Benjamin Moses; Sheila Marty Yanestria; Kartika Afrida Fauzia; Dea Anita Ariani Kurniasih; Syahputra Wibowo (Open Veterinary Journal)
Background: Globally, there is an increasing frequency of community-acquired illnesses caused by extended-spectrum beta-lactamase (ESBL)-producing E. coli. The presence of ESBL-producing E. coli in livestock is a concern, considering its transmission potential to humans, effects on animal health, risks to food safety, and the widespread spread of antibiotic resistance in both human and animal populations.